2016
DOI: 10.1002/mats.201500095
|View full text |Cite
|
Sign up to set email alerts
|

Percolation in Two‐Dimensional Copolymer‐Solvent Systems

Abstract: In this work, the structure of a strictly 2D dense polymer film for some model copolymer systems: diblock, triblock, and random copolymers is studied. An idealized model of these macromolecular systems is developed where positions of polymer beads are restricted to vertices of a simple cubic lattice and chains are under good solvent conditions (the excluded volume is the only interaction between beads of the chain and solvent molecules). The properties of the system are determined by means of Monte Carlo simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…In recent decades, much attention has been paid to the study of self-assembly in systems of linear k-mers (particles occupying k adjacent adsorption sites) deposited on 2D lattices. A linear k-mer represents the simplest model of an elongated particle with an aspect ratio of k. Computer simulations have been extensively applied to investigate percolation and jamming phenomena for the random sequential absorption (RSA) of k-mers (see, e.g., [15,16,17] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, much attention has been paid to the study of self-assembly in systems of linear k-mers (particles occupying k adjacent adsorption sites) deposited on 2D lattices. A linear k-mer represents the simplest model of an elongated particle with an aspect ratio of k. Computer simulations have been extensively applied to investigate percolation and jamming phenomena for the random sequential absorption (RSA) of k-mers (see, e.g., [15,16,17] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…A linear k-mer represents the simplest model of an elongated particle with an aspect ratio of k. Computer simulations have been extensively applied to investigate percolation and jamming phenomena for the random sequential absorption (RSA) of k-mers (see, e.g. [15][16][17] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…[26] The percolation threshold in two-dimensional macromolecular systems has recently been extensively studied. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The influence of the chain length on the threshold has also been determined: the threshold decreases rapidly for short chains but then the decrease becomes slower. [29,31,35,39] It has also been suggested that the threshold strongly depends on the structure of macromolecules expressed in terms of local polymer density.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, much attention has been paid to the study of systems of linear k-mers (particles occupying k adjacent adsorption sites) deposited on 2D lattices. A linear k-mer represents the simplest model of an hard-core (completely rigid) rod-like particle with an aspect ratio of k. Computer simulations have been extensively applied to investigate percolation and jamming phenomena for the random sequential adsorption (RSA) [10] of k-mers (see, e.g., [11,12,13] and the references therein).…”
Section: Introductionmentioning
confidence: 99%